Miguel de Unamuno and Education (Journal of Parents and Teachers, 2019)
Brief statement about some reflexions about education from Miguel de Unamuno with regard to his biography, in particular in the light of his essay La enseñanza universitaria en España (University education in Spain).
Keywords: Miguel de Unamuno; education; university education